The Role of the Crown Witness in the Process of Proving Criminal Cases in Indonesia - Ismail Ghonu; Andi Muhammad Sofyan; Nur Azisa (Musamus Law Review, 2018)
The research issue focuses on the examination of crown witnesses in the process of establishing criminal cases in Indonesia. The examination of the crown witnesses is necessary because law enforcement officers find it difficult to find evidence, other than the testimony of witnesses of the perpetrators themselves in order to find material truth that can be justified. The result of the research shows that the role of the crown witness in the criminal prosecution process is very significant, that is to find the material truth, so that the fast and simple proof process fulfills the minimum standard of proof, upholds public justice against the perpetrators and determines the demands of each actor in accordance with its role. The need for legal protection against the crown witness and the need for a policy of reform of criminal procedure law through the refinement of the Criminal Procedure Code relating to the content of witness material of the crown firmly and limitatively in the future.